2015
DOI: 10.1016/j.bone.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement for craniofacial skeletal defects and craniosynostosis in murine hypophosphatasia

Abstract: Hypophosphatasia (HPP) is an inborn-error-of-metabolism disorder characterized by deficient bone and tooth mineralization due to loss-of function mutations in the gene (Alpl) encoding tissue-nonspecific alkaline phosphatase (TNAP). Alpl−/− mice exhibit many characteristics seen in infantile HPP including long bone and tooth defects, vitamin B6 responsive seizures and craniosynostosis. Previous reports demonstrated that a mineral-targeted form of TNAP rescues long bone, verterbral and tooth mineralization defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 55 publications
4
28
0
Order By: Relevance
“…Of greater significance is the finding that craniosynostosis only occurs in ∼3‐week‐old Alpl −/− mice with severe cranial bone hypomineralization, as assessed quantitatively by micro‐CT. This finding corresponds well with our previous qualitative assessment that craniosynostosis occurs only in Alpl −/− mice with more severely deficient craniofacial bone mineralization (Liu et al, ). This result could indicate that craniosynostosis occurs indirectly, as a result of cellular changes that occur only in response to severely deficient cranial bone mineralization.…”
Section: Discussionsupporting
confidence: 92%
“…Of greater significance is the finding that craniosynostosis only occurs in ∼3‐week‐old Alpl −/− mice with severe cranial bone hypomineralization, as assessed quantitatively by micro‐CT. This finding corresponds well with our previous qualitative assessment that craniosynostosis occurs only in Alpl −/− mice with more severely deficient craniofacial bone mineralization (Liu et al, ). This result could indicate that craniosynostosis occurs indirectly, as a result of cellular changes that occur only in response to severely deficient cranial bone mineralization.…”
Section: Discussionsupporting
confidence: 92%
“…All μCT analysis was performed using the Microview (version ABA 2.2) analysis software. Similar to our previous work (Liu et al, 2013 , 2015 ), a region of interest (ROI) was selected for each of the bones to be analyzed (frontal, parietal, pre-sphenoid, basi-sphenoid, basi-occipital and mandible) (Figures S1B–D). For the frontal bone, a 0.5 mm × 0.5 mm area was located 1.5 mm anterior to the intersection point of coronal suture and sagittal suture and 1 mm lateral to the posterior frontal suture.…”
Section: Methodsmentioning
confidence: 99%
“…Neural crest-derived calvarial osteoblasts from the frontal bone have superior intrinsic osteogenic potential and tissue regeneration ability compared to mesoderm-derived calvarial osteoblasts from parietal bone (Quarto et al, 2010 ). Our previous studies suggested that there is increased bone volume and density in mesoderm derived parietal bone compared to neural crest derived frontal bone at early postnatal stage in both BALB/c congenic mice at 1 month of age (Liu et al, 2013 ) and 50% C57BL/6-50%129SF2/J mice at 2 weeks of age (Liu et al, 2015 ). However, a thorough knowledge of quantitative differences in bone parameters during postnatal development between neural crest-derived skull bone and mesoderm-derived skull bone is lacking.…”
Section: Introductionmentioning
confidence: 98%
“…Patients with severe HPP receiving asfotase alfa still often require craniotomies [ 101 ] to relieve intracranial pressure. However, asfotase alfa [ 102 ] and ChimAP [ 103 ] (a soluble chimeric form of human ALP), both can prevent craniosynostosis, at least in mice (vide infra), if treatment starts at birth. So, prevention of craniosynostosis may depend on the time of initiation of the treatment, although there are data to indicate that in humans craniosynostosis may begin during embryonic life [ 104 ].…”
Section: What We Don’t Yet Understand About Hppmentioning
confidence: 99%
“…In untreated KO mice, multiple cranial vault and facial bones lacked adequate mineralization on μCT that was not evident in the treated mice. Digital caliper linear measurements demonstrated that treatment improved nose length, nasal bone length, and frontal bone length [ 102 ].…”
Section: Preclinical Evaluation Of Bone-targeted Ezrt For Hppmentioning
confidence: 99%